2021
DOI: 10.1088/1361-665x/abd4fc
|View full text |Cite
|
Sign up to set email alerts
|

Development of a magnetorheological isolator with variable damping and variable stiffness for broadband vibration suppression

Abstract: This paper presents the damping and stiffness characteristics of a magnetorheological (MR) isolator with variable damping and variable stiffness (VDVS) for broadband vibration suppression. The MR VDVS isolator is composed of a squeeze-mode MR fluid unit and a shear-mode MR elastomer unit to obtain controllable damping force and stiffness simultaneously. Comparing with the MR fluid device in shear mode and valve mode, the device in squeeze mode can provide large controllable damping force and good energy dissip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…where ∆W is the energy dissipation per cycle, F is the damping force, and x is the displacement of the top plate. When subjected to a harmonic excitation, the equivalent viscous damping coefficient of the GERF damper can be expressed as [42,43]:…”
Section: Damping Coefficient Identification Of the Gerf Dampermentioning
confidence: 99%
“…where ∆W is the energy dissipation per cycle, F is the damping force, and x is the displacement of the top plate. When subjected to a harmonic excitation, the equivalent viscous damping coefficient of the GERF damper can be expressed as [42,43]:…”
Section: Damping Coefficient Identification Of the Gerf Dampermentioning
confidence: 99%
“…For instance, it revealed that long-term suffering of drivers from vibration could induce diseases such as lumbago, backache, and lower-back pain [1,2]. To reduce the influence of the undesirable vibration, various methods have been developed to address it, such as vibration reduction by using advanced devices and control algorithms [3][4][5][6][7][8], vibration absorption by attaching absorbers to the vibration body [9][10][11], and vibration isolation by arranging isolators between the vibration source and the protected structure [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al [23] analyzed the vehicle dynamic performance of high-speed trains with different wheel-rail contact states using variable stiffness and damping semiactive suspension magnetorheological yaw dampers. Yu et al [24] devised the magnetorheological isolator with variable damping and variable stiffness (MR VDVS) and developed an algebraic parametric model to predict its hysteretic characteristics. Peng et al [25,26] found that cubic damping vibration isolator had advantages only in some special cases.…”
Section: Introductionmentioning
confidence: 99%